Financing Long-Term Care: Ex-ante, Ex-post or Both? - Joan Costa-i-Font; Christophe Courbage; Katherine Swartz (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper examines the heterogeneity in the public financing of long-term care (LTC), and the wide-ranging instruments in place to finance long-term care services. We distinguish and classify the institutional responses to the need for LTC financing as ex-ante (occurring prior to when the need arises, such as insurance) and ex-post (occurring after the need arises, such as public sector and family financing). Then we examine country-specific data to ascertain whether the two types of financing are complements or substitutes. Finally, we examine exploratory cross-national data on public expenditure determinants, specifically economic, demographic and social determinants. We show that although both ex-ante and ex-post mechanisms exist in all countries with advanced industrial economies and despite the fact that instruments are different across countries, ex-ante and ex-post instruments are largely substitutes for each other. Expenditure estimates to date indicate that the public financing of long-term care is highly sensitive to a country's income, ageing of the population, and the availability of informal caregiving.
Keywords: I18; H50; J10; 330; long term care; long term care expenditures; long-term care insurance; social insurance; ex-ante funding; ex-post funding